Analysis of Financial Ratios in Predicting Financial Distress of Technology Companies after Covid-19 on the IDX - Sosro Hadi Wijoyo, Handoko (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This study aims to analyze the effect of liquidity ratios, solvency, profitability, activity, growth on the occurrence of financial distress in technology companies in 2022. The data analysis technique uses PLS (Partial Least Square) with the aim of predicting the large influence of Current Ratio, Debt to Asset Ratio (DAR), Debt to Equity Ratio, ROA, ROE, NPM, Receivable Turn Over, Growth Ratio to financial distress as seen from the EPS value is negative in 1 year. The results of testing the hypothesis that the liquidity ratio shows a positive but not significant effect on the occurrence of financial distress, while the solvency ratio and growth ratio show a significant positive, then the activity and profitability ratios show a significant negative effect on financial distress, Judging from the R-Square value, the contribution of the influence of liquidity, solvency, profitability, activity, growth to financial distress is 32.5%.